Evaluation of the public pipe-borne water supply in Ilorin West Local Government Area of Kwara State, Nigeria - Rafiu Babatunde Ibrahim; Emmanuel Adigun Toyobo; Samuel Babatunde Adedotun; Sulaiman Yunus (Economic and Environmental Studies (E&ES), 2018)
This paper assesses the residents' access to public pipe-borne water in Ilorin West Local Government Area of Kwara State, Nigeria. The authors analyzed spatial distribution and functionality of public pipe-borne water. They also examined intra-urban variation in the distribution of public pipe-borne water in the study area. The study used primary data which were obtained through random sampling techniques of 400 households, using structured questionnaire in the twelve political administrative wards of the examined area. Physical enumeration was also adopted to identify the functional and non-functional public pipe-borne water points. Descriptive statistics in the form of frequency table and percentages with chi-square were used to describe residents' demand and accessibility of public pipe-borne water. Analysis of Variance (ANOVA) was used to examine intra-urban variations in the functionality of public pipe-borne water. The results revealed that distribution of public pipe-borne water cut across different localities in the twelve political administrative wards that Ilorin West Local Government consisted of. Although the highest proportion (60.24%) of public pipe-borne water points were observed to be functioning, a significant proportion (39.26%) were not functioning. The highest proportion (95.5%) of the respondents were of the opinion that public pipe-borne water is not regularly available. The findings from Analysis of Variance (ANOVA) revealed significant differences (F=2.702, P=0.004) in the functioning of public pipe-borne water infrastructural elements existing in the examined area. The study concludes by suggesting the need for the government to ensure regular public water supply to meet the residents' daily needs for water consumption and domestic use, which continue to increase every day.
Keywords: I38; R22; 330; Public Pipe- Borne water; Water distribution